Heteragrion lencionii (Odonata: Heteragrionidae) sp. nov. from Serra de Itabaiana National Park, Northeastern Brazil - Vilela, Diogo Silva; Farias, Antonio Bruno Silva; Santos, Jean Carlos (Zootaxa, 2021)
The Neotropical genus Heteragrion Selys, 1862 is one of the most speciose among Zygoptera. Notwithstanding, most of its species are poorly known, especially those from undersampled areas such as Northeastern Brazil. Here, we describe Heteragrion lencionii sp. nov., from protected areas of Sergipe state (Holotype ♂, Brazil, Sergipe, Areia Branca, Serra de Itabaiana National Park, -10.7484, -37.3390, 179 m, 7.xii.2020, A.B. Farias & A.E. dos Santos leg., in UFS). This is only the second Heteragrion species discovered as new for the Northeastern region of Brazil, separated from other congeners by cercus morphology and thoracic coloration pattern.